Implementation of discretized vector control strategies for induction machines - Nishat, MD. Inoon; Chowdhury, Amalesh (My University, 2012)
This report has been written about the project work where different control strategies have been investigated and then implemented on a digital signal processor through which a converter-operated-induction-machine is controlled. The findings are also investigated according to theory and comparing with simulations. This project work has been done for the fulfillment of master's degree under Electric Power Engineering department starting from 22nd September 2010. In this master’s thesis work three control schemes for an induction machine are implemented on the dSPACE DS 1103 real time control system, through which a converter operated induction machine is controlled. Both open loop control and closed loop Field Oriented Current control are implemented on the system. The controllers are implemented by writing c-programs and all the control commands are given from the ControlDesk software using a real time environment. With the sensors used by the controllsystem, real time measurements are taken with the Controldesk software and the data from the experiments are saved and compared with simulations. The open loop control (V/Hz control) has been implemented successfully and the output is almost similar to the theory. From the open loop experiments it is found that the hardware is working well and that the measuring system is working, even though there are some offsets in the signals and some measurement noise in the signals from the switching. For the field oriented current control system the low current step of 0.33 A has been successful and it matches with the simulations. The rise time of the current is 2.2 ms, as designed, and the current follows the reference without any overshoot. But the responses for the larger steps of 0.833A and 1.7A do not match with the simulated step responses. The rise time of the measured current is faster due to the second order response and that the control system is implemented digitally. For the speed controller the measured step response matches with the simulated one, except for that the measured response has oscillations, which are not present in the simulations. The second order response comes partly from the low pass filter which is used to remove the noise in the speed signal is not included in the controller design. The selected cut off frequency of 10 Hz affected the speed controller with a bandwidth of 20 rad/s. The flexible rubber coupling that connects the two machines in the experimental setup could also contribute to the second order response. From simulations it could be observed that increasing the cut off frequency to 200 rad/s or lowering the bandwidth of the speed controller to 10 rad/s the second order behavior could be efficiently removed. By reducing the speed controller bandwidth to 10 rad/s in the experimental setup the oscillations in the step response could be damped.
Keywords: Elkraftteknik; Electric power engineering